May Measurement Month 2017: Results of 39 national blood pressure screening programmes. (24th April 2019) - Poulter, Neil R; Borghi, Claudio; Castillo, Rafael R; Charchar, Fadi J; Ramirez, Agustin J; Schlaich, Markus P; Schutte, Aletta E; Stergiou, George; Unger, Thomas; Wainford, Richard D; Beaney, Thomas
Abstract: Raised blood pressure is the biggest single risk factor responsible for mortality worldwide. Despite this, the majority of people with hypertension are unaware of having it, are untreated, or are on treatment but uncontrolled. May Measurement Month is a global campaign initiated by the International Society of Hypertension with the aim of raising awareness of high blood pressure. In the first year of the campaign in 2017, over 1.2 million people were screened in 80 countries across the world, finding over 100 000 people with hypertension who were not on treatment and over 150 000 people on anti-hypertensive treatment who were not controlled. The individual national results from 39 countries are presented in this supplement. In this article, we discuss the background to the campaign, along with some of the logistical and methodological challenges that were faced in setting up the campaign, and in collecting and analysing the data from such a large cross-sectional study. With the lessons learned from the 2017 campaign, the campaign was repeated in 2018 and is to be repeated again in 2019.